Magnetron-Sputtered Amorphous Carbon Films for Aluminium Proton-Exchange-Membrane Fuel Cell Bipolar Plates - Parnia Navabpour; Kun Zhang; Giuseppe Sanzone; Susan Field; Hailin Sun (Physchem)
Aluminium is an attractive material for proton-exchange-membrane fuel cell bipolar plates as it has a much lower density than steel and is easier to form than both steel and graphite. This work focused on the development of amorphous carbon films deposited using closed-field unbalanced magnetron sputtering (CFUBMS) in order to improve the corrosion resistance of aluminium bipolar plates and to enhance fuel cell performance and durability. Chromium and tungsten adhesion layers were used for the coatings. It was possible to achieve good electrical conductivity and high electrochemical corrosion resistance up to 70 °C on polished Aluminium alloy 6082 by tuning the deposition parameters. Coatings with a tungsten adhesion layer showed better corrosion resistance than those with a chromium adhesion layer. In situ, accelerated stress testing of single cells was performed using uncoated and coated Al6082 bipolar plates. Both coatings resulted in improved fuel cell performance compared to uncoated aluminium when used on the cathode side of the fuel cell.